First patient diagnosed as feingold syndrome type 2 with alport syndrome and review of the current literature - ARMAN, AHMET; ATA, PINAR; SÖYLEMEZ, MEHMET ALİ (My University, 2022)
Introduction: Feingold syndrome type 2 (FGLDS2) is an ultra-rare genetic disorder characterized by short stature, microcephaly, digital abnormalities, and intellectual disability. Until now, 22 patients have been reported in the literature. FGLDS2 is caused by a germline heterozygous deletion of 13q resulting in haploinsufficiency of the MIR17HG gene. Case report: In the present study, we evaluated clinical, radiological, and genetic analyses of a 10-year-old Turkish-origin girl with short stature, brachydactyly, intellectual disability, hematuria, and proteinuria. Conclusion/Discussion: In the array-CGH analysis, a 15.7-Mb deletion, arr[hg19] 13q22q31.3(78,241,132_93,967,288)x1, was detected, and this alteration was evaluated to be pathogenic. The deletion of this region covering the MIR17HG gene is a potential cause of FGLDS2. Also, at her clinical exome sequencing study, a heterozygous c.2023G>A p.(Gly675Ser) variation was detected in the COL4A5 gene (NM_000495.4) that was likely pathogenic in up-to-date databases. As a result, we report on a patient who has FGLDS2 and Alport syndrome. This is the first report of a Turkish-origin FGLDS2 patient. Reporting new cases expands the range of phenotypes, plays a crucial role in understanding the FGLDS2 pathogenesis, and is important in terms of screening at-risk family members for giving appropriate genetic counseling and preimplantation genetic diagnosis opportunities.
Keywords: Tıp; Sağlık Bilimleri; Dahili Tıp Bilimleri; Tıbbi Genetik; Yaşam Bilimleri; Moleküler Biyoloji ve Genetik; Temel Bilimler; Medicine; Health Sciences; Internal Medicine Sciences; Medical Genetics; Life Sciences; Molecular Biology and Genetics; Natural Sciences; GENETİK VE KALITIM; Moleküler Biyoloji ve Genetik; Yaşam Bilimleri (LIFE); GENETICS & HEREDITY; MOLECULAR BIOLOGY & GENETICS; Life Sciences (LIFE); Genetik; Moleküler Biyoloji; Genetik (klinik); Genetics; Molecular Biology; Genetics (clinical); Feingold syndrome type 2; MIR17HG; Hematuria; Proteinuria; GENOTYPE-PHENOTYPE CORRELATIONS; NATURAL-HISTORY; 195 FAMILIES; MICRODELETION; MUTATIONS; DELETION; CLUSTER; COL4A5; Feingold syndrome type 2; MIR17HG; Hematuria; Proteinuria; COL4A5